Allergy evaluation after emergency treatment: anaphylaxis to the over-the-counter medication clobutinol. Issue 3 (9th March 2007) - Seitz, Cornelia S; Bröcker, Eva-B; Trautmann, Axel
Abstract : Anaphylaxis is traditionally diagnosed and treated as an acute emergency but should be always followed by a search for specific triggers, resulting in avoidance strategies. This case report highlights the relevance of a detailed evaluation after anaphylaxis for diagnosis of a rare but potentially life-threatening allergy. Considering the high frequency of clobutinol application, IgE-mediated allergic hypersensitivity seems extremely rare and has to be distinguished from infection-associated urticaria and angioedema as well as non-specific summation effects. Accidental re-exposure has to be strictly avoided and therefore after identification of clobutinol as the anaphylaxis trigger, the patient received detailed allergy documents including international non-proprietary and trade names of the culprit drug.